REMOTE SENSING TECHNIQUES IN EARTH AND ENVIRONMENTAL APPLICATIONS: MALAYSIA CONTEXT - Nurul Hazrina Idris, editor 365539; Nurul Hawani Idris, 1981-, editor 285542; Nurul Hazrina Idris, contributor 285542; Nurul Nadiah Yahya, contributor 305069; Abdul Wahid Rasib, 1970-, contributor 257446; Nurul Hawani Idris, 1981-, contributor 285542; Muhammad Zulkarnain Abd. Rahman, contributor 561421; Wan Hazli Wan Kadir, contributor 281031; Md. Zamri Md. Ismail, contributor 191635; Othman Zainon, 1973-, contributor 513547; Ani Hassan Md. Din contributor 647818; Astina Tugi, 1991-, contributor 605079; et al. (Johor Bahru, Johor : Penerbit UTM Press, 2017)
Includes bibliographical references and index.